FRI0615 Normalised toxicity to pregabalin did not increase with changes in approval mechanism and use in australia. (12th June 2018) - McMaster, C.; Liew, D. F. L.; Joules, E.; Robinson, J.; Greene, S.; Buchanan, R. R. C.; Frauman, A. G.
Abstract : Background: Pregabalin is a potent antagonist of neuronal voltage-gated calcium channels used to treat neuropathic pain. Although first registered with the Therapeutic Goods Administration (TGA) in April 2005, rapid uptake of pregabalin in the Australian market only came after its listing on the Pharmaceutical Benefits Scheme (PBS) with a streamlined code on 1st March 2013 for the indication of neuropathic pain. Recently, there has been concern raised about the growing off-label use of pregabalin for chronic pain syndromes and the subsequent potential for undue adverse drug reactions (ADRs). 1 Objectives: The aim of this study was to measure how broadening access to pregabalin in Australia affected the rate of pregabalin-associated ADRs, and whether such an effect was disproportionate to the change in pregabalin prescription rates. Methods: We extracted ADRs reported in the TGA Database of Adverse Event Notifications (DAEN) between 1st January 2009 and 18th October 2017, in which pregabalin was thought to have been causative. We also extracted calls to the Victorian Poisons Information Centre (VPIC) between 1st January 2009 and 31st December 2017 in which pregabalin was a reported exposure. For both databases, ADR rates were annualised, with the missing DAEN ADR reports between 19th October 2017 and 31st December 2017 imputed using a linear model based on year-to-date ADR rates. The annual ADR rates were normalised by dividing by the estimated number of pregabalin prescriptions filled (in millions), to obtain a normalised Toxicity Index (number of ADRs per million scripts). Because the data was annualised, the 1st January 2013 was used as the approximate starting date of PBS streamlined listing. Results: The estimated number of pregabalin prescriptions filled in Australia increased over the study period from 155, 336 in 2009 to 3, 739, 421 in 2017. A total of 886 ADRs were reported to VPIC over the study period, and 1056 reported to DAEN (1076 after extrapolation). The mean Toxicity Index (TI) for the VPIC database was 539 ADRs/million scripts before PBS streamlined listing, and 298 ADRs/million scripts after; there was no evidence that the TI had increased (p=0.9, one-tail t-test). Similarly, the TI for the DAEN database was 441 ADRs/million scripts prior to PBS streamlined listing, versus 85 ADRs/million after; there was no evidence that TI increased (p=0.98, one-tail t-test). Conclusions: After adjusting for the total volume of scripts dispensed, the rate of ADRs involving pregabalin in both the VPIC and DAEN databases did not increase after a streamlined approval mechanism was adopted, leading to significantly increased use. These data do not support the emergence of undue adverse drug reactions from increased off-label use of pregabalin. Reference: 1. Goodman CW, Brett AS. Gabapentin and Pregabalin for Pain—Is Increased Prescribing a Cause for Concern?New England Journal of Medicine2017;377(5):411–414. doi:10.1056/NEJMp1704633 Disclosure of Interest: None declared